Revision der paläarktischen Arten der Gattung Dapsilarthra. 1. Beitrag zur systematischen Bearbeitung der Alysiinae (Hymenoptera: Braconidae). - Königsmann, Eberhard (Contributions to Entomology = Beiträge zur Entomologie, 1959)
The author gives a revision of the palaearctic species of Dapsilarthra (the name Adelura being homonymous with a bird genus). A new species, D. nowakowskii, reared from Phytomyza minuscula Gour., is described. Nomenclatural Actsbalteata (Thomson, 1895) (Dapsilarthra), Lectotype described as Alysia (Adelura) balteatanowakowskii Königsmann, 1959 (Dapsilarthra), spec. n.